TETAP BERTAHAN DI TENGAH KRISIS: SUATU KAJIAN TEORITIS - Kurniawati, Dyah (Widya Warta, 2010)
Global financial crisis creates some crucial impacts for Indonesia. A lot of companies are forced to fire their employees significantly, as an effect of the decline of foreign demand on Indonesian products. Besides the impacts on financial and banking sectors, global financial crisis also causes some great problems on industrial sectors, which employ so many workers, such as mining, energy, textile, garment, shoes, automotive, and food-beverage industries. For Indonesian companies, the problems become greater because of the increase of credit interest offered by commercial banks (in line with the increase of Indonesia Central Bank rates), less credit realization, and the decrease of peoples’ purchasing power. There are four alternatives for the companies to survive in the crisis: (1) being defensive more than offensive, (2) giving priority to prospective customers, (3) being creative, and (4) optimalizing domestic markets.